Novel frameshift variant of WNT10A in a Japanese patient with hypodontia - Michiyo Ando; Yoshihiko Aoki; Yasuto Sano; Junya Adachi; Masatoshi Sana; Satoru Miyabe; Satoshi Watanabe; Shogo Hasegawa; Hitoshi Miyachi; Junichiro Machida; Mitsuo Goto; Yoshihito Tokita (Human Genome Variation)
Abstract Congenital tooth agenesis is caused by the impairment of crucial genes related to tooth development, such as Wnt signaling pathway genes. Here, we investigated the genetic causes of sporadic congenital tooth agenesis. Exome sequencing, followed by Sanger sequencing, identified a novel single-nucleotide deletion in WNT10A (NC_000002.12(NM_025216.3):c.802del), which was not found in the healthy parents of the patient. Thus, we concluded that the variant was the genetic cause of the patient’s agenesis.